2021
DOI: 10.1177/09603271211017324
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of biomarkers in diagnosis of asbestos-induced malignant pleural mesothelioma

Abstract: Introduction: Malignant pleural mesothelioma (MPM) is a malignant tumor that is associated mostly with asbestos exposure. The present study was to evaluates the diagnostic value of neopterin, periostin, YKL-40, Tenascin-C (TNC), and Indolamine 2,3-dioxygenase (IDO) as noninvasive markers of malign pleural mesothelioma. Methods: Included in the study were 30 patients diagnosed with malign pleural mesothelioma, and 25 people as a control group. Biomarker levels were determined using an enzyme immunoassay . A Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It was reported that infection of Paragonimus kellicotti in Syrian hamsters induced reactive mesothelial hyperplasia (Weina and Burns 1992). Another chitinase-like protein, CHI3L1/YKL-40, is reportedly a useful biomarker for malignant pleural mesothelioma as well as lung cancer and asbestosis (Corradi et al 2013;Tanriverdi et al 2021). Although the function of mesothelial cells during parasitic infection is still unknown, up-regulated Ym1 in mesothelial cells may be involved in the regulation of immune response against parasitic infection by recruiting leukocytes into the pleural and peritoneal cavities.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that infection of Paragonimus kellicotti in Syrian hamsters induced reactive mesothelial hyperplasia (Weina and Burns 1992). Another chitinase-like protein, CHI3L1/YKL-40, is reportedly a useful biomarker for malignant pleural mesothelioma as well as lung cancer and asbestosis (Corradi et al 2013;Tanriverdi et al 2021). Although the function of mesothelial cells during parasitic infection is still unknown, up-regulated Ym1 in mesothelial cells may be involved in the regulation of immune response against parasitic infection by recruiting leukocytes into the pleural and peritoneal cavities.…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising as several of the identified proteins previously are associated with various cancers, including MPM (Table 5). For example, the increased expression of nipped-B-like protein is significantly linked with poor prognosis, tumor differentiation, and lymph node metastasis in non-small cell lung cancer [20], Beta ig-h3 plays a role in mesothelioma tumorigenesis and progression [21], periostin, haptoglobin, protein AMBP fragments are upregulated in various cancers including MPM [22][23][24], whereas galectin-3 binding protein are associated to prognosis and progression of various cancers [25]. Present in our dataset were also the proteins fibulin-3 and mesothelin-both originally proposed as biomarkers for MPM [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mesothelioma cells increase the expression of L-type Amino acid Transporter 1 (LAT1), depriving T-cells of amino acids, such as arginine and tryptophan, which are essential for T-cell function and proliferation [ 121 ]. Mesothelioma cells could also inhibit T-cell glycolysis and functions, increasing the levels of indoleamine-pyrrole 2,3-dioxygenase (IDO), which degrades tryptophan into kynurenine, a well-known immunosuppression factor [ 121 , 123 , 124 ]. In conclusion, the mesothelioma metabolome and secretome equally recruit and reprogram infiltrating immune cells [ 122 ].…”
Section: Mesothelioma Microenvironment: Tumor–host Crosstalk Driving ...mentioning
confidence: 99%